THORACIC TUBERCULOUS SPONDYLITIS WITH DECOMPRESSION AND POSTERIOR STABILIZATION TREATMENT: A CASE REPORT - Desdiani, Desdiani (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Tuberculosis (TB) spondylitis is one of the most common spinal infections. The management of spinal tuberculosis is difficult due to non-specific and variable clinical manifestation that leading to delayed identification and increases the risk of disease. The early identification and treatment are very important to avoid permanent damage in the future. Method. In this research, the researcher reports a case of a patient with tuberculous spondylitis involving the thoracic vertebral body which treated by decompression and posterior stabilization treatment. Results and Analysis. The physical examination revealed a mass appears in the midline of the back. Chest CT examination without contrast revealed a mass that caused destruction and compression of the right side of the Thoracal 7 (Th 7) vertebral body, partial destruction of the right Th7 lamina, and spinal intracanal pushing to the left of the Th7 level of the spinal cord which caused the destruction of 7th and 8th posteromedial right ribs nearby. During the two months of treatment, the patient was treated with a first-line oral regimen as standard treatment for extrapulmonary TB followed by seven-month follow-up phase. At follow-up after more than 2 months of initial TB drug administration, the back pain was persisted. The patient underwent level 7 thoracic decompression by means of laminectomy and flavectomy. Histopathological examination from biopsy showed fibrous connective tissue containing epitheloid tubercles with datia langhans which suggests the presence of tuberculous spondylitis.  The diagnosis was confirmed by AFB staining. Discussion. This case is important to provide recognition of the risks and phenomena of the continuing incidence of spinal TB, despite the progress made in early diagnosis and effective management.